Impact on quality of life in patients with dermatophytosis. (6th November 2019) - Mushtaq, Sabha; Faizi, Nafis; Amin, Syed S.; Adil, Mohammad; Mohtashim, Mohammad
Abstract: Background/Objectives: Dermatophytosis can have a significant effect on patient's psychosocial and economic life. Despite this, knowledge on the quality of life (QoL) in patients with dermatophytosis is limited. The objective of the present study was to assess the quality of life in patients with dermatophytosis. Methods: This was a cross‐sectional study conducted in the Department of Dermatology at a tertiary care hospital from August 2018 to December 2018. All the patients with dermatophytosis aged ≥16 years were included and evaluated for impact on quality of life. The association of Dermatology Life Quality Index (DLQI) scores with disease characteristics was assessed using t ‐test, ANOVA and Pearson's correlation test, as applicable. Results: A total of 348 patients were analysed. The mean ± SD DLQI score in our study was 13.4 ± 7.3. Dermatophytosis was found to have a very large effect on the QoL in majority (44.8%) of our patients. DLQI questions pertaining to symptoms and feelings and daily activity had the highest impact on patients. The DLQI score was significantly affected by the number of sites involved ( P  < 0.001), body surface area ( P  < 0.001) and the severity of symptoms ( P  = 0.007). Conclusion: Dermatophytosis was found to have a significant impact on the QoL of affected patients. The DLQI score was influenced by the severity of the disease. This study also underscores the feasibility of DLQI score based QoL assessment in dermatophytosis.